The association between caregiver burden and sleep disturbances in partners of patients with Parkinson's disease. - Happe, Svenja; Berger, Klaus (Age & Ageing, 2002)
|WbObjectives:[|WB] caregivers of patients with various diseases frequently report sleep disturbances and depressive symptoms. Care intensity for individuals with Parkinson's disease is mainly influenced by the severity of their motor impairment. The latter is associated with sleep fragmentation, nocturnal pain and cramps. These disease-specific characteristics contribute to sleep-related problems in patients. However, little is known about prevalence and causes of sleep disturbances in caregivers of Parkinson's disease patients. |WbDesign and setting:[|WB] cross-sectional analysis, nested within the FAQT-Study, a prospective German cohort study evaluating determinants of quality of life in Parkinson's disease patients. |WbParticipants:[|WB] we assessed 106 Parkinson's disease patients and their caregiving partners. |WbMeasurements:[|WB] patients and partners were asked to fill in the Center for Epidemiologic Studies Depression Scale, the caregiver burden inventory, and the Giessener Beschwerdebogen of psychosomatic complaints. All instruments include questions about sleep related problems. Patients were examined by neurologists and classified according to established scales (UPDRS and Hoehn and Yahr scales). |WbResults:[|WB] frequent sleep disturbances were reported by 27% of all spouses. Relevant depressive symptoms were shown in 30% of spouses and 45% of Parkinson's disease patients (P<0.001). Depression scores in partners correlated with those in patients. Self-perceived bad night-time sleep in spouses was related to symptom severity, male gender, bad sleep in patients, and to the frequency of caregiving. Caregiver burden was identified as a mediator of the association between care intensity and bad sleep, while psychosomatic complaints were related to sleep problems independently. |WbConclusion:[|WB] sleep disturbances are prevalent in partners of Parkinson's disease patients and influenced by their engagement in the caregiving process. Treatment optimization for motor symptoms in patients may not only contribute to improved patient sleep but also to a lower prevalence of sleep disturbances in caregivers. Reprinted by permission of the publisher.